La tragedia de las economías negadas: una breve historia de dos emprendedores - Laurent Solís, Paul (2015)
This article addresses the history of Juan Mezzich, a European immigrant who came to Peru to start a wine business, and his grandson, Julio Cesar Mezzich, a leader of Shining Path. Throughout the article, the author describes the historical period and the economic and social context in which both characters developed, emphasizing the role of the regulation of the economy that the Peruvian state ran throughout the twentieth century.